2017
DOI: 10.1080/14767058.2017.1387532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early supplementation with low-dose aspirin on functional first trimester parameters in low-risk pregnancies

Abstract: Even though the results are not always statistically significant, they demonstrate that placentation parameters improve with higher doses of aspirin started before 11 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…UTIs are caused by different type of bacteria which invades the local environment, then multiply, thus causing the symptomatology. Gender prevalence of UTIs is well known higher in women due to particularly anatomic characteristics of the urinary tract such as shorter urethra, the proximity of the anus and sexual activity [5,48]. Some studies reveal that 1 of 3 women receive specific treatment for UTIs before 24 years and about 40% to 50% develop one UTI during lifetime which leads to high economic costs [12].…”
Section: Resultsmentioning
confidence: 99%
“…UTIs are caused by different type of bacteria which invades the local environment, then multiply, thus causing the symptomatology. Gender prevalence of UTIs is well known higher in women due to particularly anatomic characteristics of the urinary tract such as shorter urethra, the proximity of the anus and sexual activity [5,48]. Some studies reveal that 1 of 3 women receive specific treatment for UTIs before 24 years and about 40% to 50% develop one UTI during lifetime which leads to high economic costs [12].…”
Section: Resultsmentioning
confidence: 99%
“…Aspirin has a good safety profile, with no increase in haemorrhagic complications [ 35 ]. It has been proven beneficial for high-risk women with a reduction of up to 80% (with good compliance) of pre-eclampsia development and has also been associated with improving functional placentation parameters even in low-risk pregnant patients when started in early pregnancy [ 36 , 37 ]. As for financial reasons, universal aspirin treatment was associated with the lowest costs compared to screening using biochemical and ultrasound markers, screening using patients’ characteristics and history, or not giving aspirin at all [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose aspirin is used to inhibit platelet aggregation and prevent pre-eclampsia. 17 Due to the similarity between the mechanisms of spontaneous PTL and pre-eclampsia, it has been suggested that lowdose aspirin may also be used to prevent spontaneous PTL. Some studies have performed secondary analyses of data on the effect of low-dose aspirin on the prevention of preeclampsia to evaluate the effect of low-dose aspirin on the prevention of PTL.…”
Section: Introductionmentioning
confidence: 99%